2018
DOI: 10.1088/1674-1056/27/1/010303
|View full text |Cite
|
Sign up to set email alerts
|

Quantum speed limit time of a two-level atom under different quantum feedback control

Abstract: We investigate the quantum speed limit time (QSLT) of a two-level atom under quantum-jump-based feedback control or homodyne-based feedback control. Our results show that the two different feedback control schemes have different influences on the evolutionary speed. By adjusting the feedback parameters, the quantum-jump-based feedback control can induce speedup of the atomic evolution from an excited state, but the homodyne-based feedback control cannot change the evolutionary speed. Additionally, the QSLT for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It means that when QSL time is shortened, the speed of the quantum evolution will increase. Too much efforts have been done to obtain a short QSL time [17][18][19][20]. It has been shown that memory effects in non-Markovian dynamics of open quantum systems can reduce the QSL time [21].…”
Section: Introductionmentioning
confidence: 99%
“…It means that when QSL time is shortened, the speed of the quantum evolution will increase. Too much efforts have been done to obtain a short QSL time [17][18][19][20]. It has been shown that memory effects in non-Markovian dynamics of open quantum systems can reduce the QSL time [21].…”
Section: Introductionmentioning
confidence: 99%
“…Markovian quantum feedback control introduced by Wiseman and Milburn [21,22] has been widely used to feed back measurements to the system to modify the future dynamics of the system, such as suppressing decoherence, [23][24][25][26] protecting quantum correlations, [27] improving steady state entanglement, [28][29][30][31][32][33] manipulating the geometric phase [34] and stationary state [35] of the dissipative two-level system, preparing a three-atom singlet, [36] W state, and GHZ state, [37,38] and enhancing the accuracy of parameter estimations. [39] Recently, quantum-jump-based feedback control has been used to accelerate quantum evolution, [40] enhance exciton transmission, [41] study on the dissipative stabilization of multipartite entanglement with Rydberg atoms, [42] maneuver Einstein-Podolsky-Rosen Steering, [43] and so on. According to different measurement strategies, homodyne-based and quantum-jump-based feedback controls are proposed.…”
Section: Introductionmentioning
confidence: 99%